2016
DOI: 10.1007/s10113-016-0929-z
|View full text |Cite
|
Sign up to set email alerts
|

Decline of woody vegetation in a saline landscape in the Groundnut Basin, Senegal

Abstract: Several studies have documented that vegetation in the Sahel is highly dynamic and is affected by the prevailing climatic conditions, as well as by human use of the areas. However, little is known about vegetation dynamics in the large saline areas bordering the rivers of West Africa. Combining satellite imagery, the perception of local people and botanical information, this study investigated the vegetation dynamics and the drivers of vegetation changes in Fatick Province, Senegal. Satellite images showed a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
(66 reference statements)
3
8
0
Order By: Relevance
“…This is in line with findings from questionnaire-based surveys among elderly people in the Sahel (e.g. Rasmussen et al, 2001;Gonzales et al, 2004Gonzales et al, , 2012Ouedraogo et al, 2010;Brandt et al, 2014c;Sambou et al, 2016) documenting a clear increase in robust woody species at the expense of more mesic species. The survey periods cover at least 20 years up to more than 40 years.…”
Section: Contributions Of Other Authorssupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with findings from questionnaire-based surveys among elderly people in the Sahel (e.g. Rasmussen et al, 2001;Gonzales et al, 2004Gonzales et al, , 2012Ouedraogo et al, 2010;Brandt et al, 2014c;Sambou et al, 2016) documenting a clear increase in robust woody species at the expense of more mesic species. The survey periods cover at least 20 years up to more than 40 years.…”
Section: Contributions Of Other Authorssupporting
confidence: 91%
“…Rasmussen et al, 2001;Gonzales et al, 2004Gonzales et al, , 2012Ouedraogo et al, 2010;Brandt et al, 2014c;Sambou et al, 2016;Sect. 4.2);…”
Section: Contributions Of Other Authorsmentioning
confidence: 99%
“…This is in line with findings from questionnaire-based surveys among elderly people in the Sahel (e.g. Rasmussen et al, 2001;Gonzales et al, 2004Gonzales et al, , 2012Ouedraogo et al, 2010;Brandt et al, 2014c;Sambou et al, 2016) documenting a clear increase in robust woody species at the expense of more mesic species. The survey periods cover at least 20 years up to more than 40 years.…”
Section: Contributions Of Other Authorssupporting
confidence: 91%
“…The contrast between a dryer western Sahel and a wetter eastern Sahel is becoming more significant (Lebel and Ali, 2009;Nicholson, 2013). Sanogo et al (2015) found a statistically significant positive rainfall trend between 1980 and 2010; however, it did not reach the degree of wetness of the 1950s.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation